2017
DOI: 10.1186/s12885-017-3642-5
|View full text |Cite
|
Sign up to set email alerts
|

MiR-9, miR-21, and miR-155 as potential biomarkers for HPV positive and negative cervical cancer

Abstract: BackgroundCervical cancer is the second leading cause of death among female patients with cancer in the world. High risk human papillomavirus has causal roles in cervical cancer initiation and progression by deregulating several cellular processes. However, HPV infection is not sufficient for cervical carcinoma development. Therefore, other genetic and epigenetic factors may be involved in this complex disease, and the identification of which may lead to better diagnosis and treatment. Our aim was to analyze t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(89 citation statements)
references
References 29 publications
5
83
0
1
Order By: Relevance
“…However, expression of the normally silent miR‐20b‐5p and other miRNA cluster members (miR‐106a‐5p and miR‐363‐3p) caused a decrease in proliferation in oral squamous cell carcinoma cells, highlighting the cancer‐specific role of certain miRNAs. We found an enrichment of miR‐9‐5p and miR‐9‐3p in HPV + EVs, which is consistent with reports of their overexpression in HPV + OPSCC and HPV + cervical cancer …”
Section: Discussionsupporting
confidence: 92%
“…However, expression of the normally silent miR‐20b‐5p and other miRNA cluster members (miR‐106a‐5p and miR‐363‐3p) caused a decrease in proliferation in oral squamous cell carcinoma cells, highlighting the cancer‐specific role of certain miRNAs. We found an enrichment of miR‐9‐5p and miR‐9‐3p in HPV + EVs, which is consistent with reports of their overexpression in HPV + OPSCC and HPV + cervical cancer …”
Section: Discussionsupporting
confidence: 92%
“…S1A), suggesting that RNU6B uniformly expressed in cervical tissue samples regardless of different disease status. Similar findings of using RNU6B as internal reference in miRNA expression studies in cervical lesions and cancer were also reported (Honegger et al, 2015;Park et al, 2017;Tian et al, 2014). After the relative quantification of miRNA expression was calculated, the fold change of the miRNA was analyzed using: 2 ÀDDCt .…”
Section: Total Rna Extraction and Mirna Detectionmentioning
confidence: 62%
“…No significant difference ( C t values) was found between three groups of samples ( P = 1.0, P = 0.26 and P = 0.08 for normal versus CIN, normal versus cancer and CIN versus cancer) (), suggesting that RNU6B uniformly expressed in cervical tissue samples regardless of different disease status. Similar findings of using RNU6B as internal reference in miRNA expression studies in cervical lesions and cancer were also reported (Honegger et al ., ; Park et al ., ; Tian et al ., ). After the relative quantification of miRNA expression was calculated, the fold change of the miRNA was analyzed using: 2normalΔnormalΔCt.…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, cancer cells could escape immune attack by downregulating NKG2D ligands including MICA, MICB, and UL16-binding protein. TAP transporter associated with antigen processing, MHC-I major histocompatibility complex class I, MICA/B MHC-I chain-related molecules A/B, IDO indoleamine 2, 3-dioxygenase, ULBP UL16-binding protein cancer (NSCLC), and glioma might contribute to enhanced immune tolerance in the tumor microenvironment [57][58][59]. Meanwhile, some endoplasmic reticulum stress-associated miRNAs such as miR-346 regulates immune response by directly targeting TAP1 or indirectly suppressing the expression of MHC-I molecules and interferon (IFN) signaling pathway [60].…”
Section: The Role Of Mirnas In Cancer Immune Evasionmentioning
confidence: 99%